Chemical recycling of mixed plastic waste via catalytic pyrolysis. Issue 5 (October 2022) - Martínez-Narro, Gerardo; Prasertcharoensuk, Phuet; Diaz-Silvarrey, Laura S.; Dixon, Liam; Phan, Anh N.
Abstract: The recovery rate of plastic waste has increased over recent years, however, there are still a large amounts of waste disposed in landfills or littered in the environment. As a result, advanced thermochemical technologies, such as catalytic pyrolysis, have become a promising approach to solve plastic waste management issues. This work aims to assess inexpensive catalysts derived from waste biomass for pyrolysis of mixed plastic waste for high-value products. Conventional thermal pyrolysis at high temperatures, i.e. 800 °C only increased the gas yield (up to 52 wt% from the 32 wt% obtained at 500 °C) but had no significant effect on the proportion of individual compounds in the gas fraction. A two-stage catalytic pyrolysis of mixed plastic waste at 600 °C (first stage) combined with biochar catalyst held isothermally at 800 °C (second stage) significantly enhanced the cracking process compared to thermal pyrolysis. In presence of the biochar catalyst, the gas yield increased up to 85 wt% mainly by an increase in the yield of hydrogen (from 0.2 wt% to 3.3 wt%) and methane (from 1.4 wt% to 55 wt%). Biochar also removed all the benzoic acid in the wax fraction. Therefore, the use of biochar derived from biomass waste as a catalyst opens-up an opportunity to develop a sustainable and efficient process to valorise waste. Highlights: Developed a sustainable process for recovery chemicals from mixed plastic waste. Obtained up to 55 wt% of methane and 3 wt% hydrogen from mixed plastic waste. Up to 90% reduction of styrene and heavy hydrocarbons (> C17 ) in liquid products. Waste biomass derived biochar promoted methane and hydrogen production. Biochar demonstrated compatible catalytic activity to commercial cracking catalysts.